Anlotinib, a novel TKI, as a third-line or further-line treatment in patients with advanced non-small cell lung cancer in China: A systemic review and meta-analysis of its efficacy and safety. Issue 23 (11th June 2021) - Ye, Haiyong; Li, Zhaoyi; Liu, Kangning; Zhang, Feng; Cheng, Zhengliang
Abstract: Purpose: In this meta-analysis and systemic review, we focused on the effectiveness and safety of anlotinib in patients with advanced non-small cell lung cancer(NSCLC). Methods: The databases of PubMed, EMBASE, Cochrane Library, CNKI, Wanfang, and CBM were searched by 2 investigators up to April 2020. Titles and abstracts of all records were screened and eligible publications were retrieved in full. Review Manager (version 5.2, Cochrane Library) was used for data analysis. The outcomes of interest were disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and treatment-related adverse event (TRAE). Data was pooled for quantitative analysis and the effect size was reported as hazard ratio for survival outcomes and odds ratio (OR) for safety outcomes, both with a random-effects model. Results: A sum of 1480 patients were included in 11 trials ranging from 2018 to 2020. Substantial improvements of PFS, OS, and DCR were observed in patients treated with anlotinib alone or in combination with other conventional treatment. Accompanied TRAE included statistically significant higher risk for hypertension (OR = 11.05, 95% confidence interval [CI] = 7.85–15.55, P < .001), hepatic dysfunction (OR = 1.96, 95% CI = 1.29–2.68, P < .001), diarrhea (OR = 2.20, 95% CI = 1.17–4.16, P < .05), and hemoptysis (OR = 2.59, 95% CI = 1.71–3.93, P < .01). Conclusions: Our study suggested that anlotinib as maintenance therapy for advanced NSCLC patients is associated with prolonged PFS and OS as well as DCR improvement, but it was accompanied by increased risk of TRAE, such as hypertension, hepatic dysfunction, diarrhea and hemoptysis. Although much effort has been made to clinical trials of anlotinib, further studies are warranted to provide more convincing evidence.